Unusual sequence element found at the end of an amplicon. - Baran, N (1987)
In a polyomavirus-transformed rat cell line, designated LPT, the polyomavirus DNA is integrated into a single chromosomal site. Treatment of LPT cells with carcinogens induces amplification of the integrated virus DNA and flanking cellular sequences. We show that the amplification is arrested within a specific cell DNA segment that maps 1.3 to 1.85 kilobases beyond one virus-cell DNA junction, defined as the left junction. We also present the sequence of an 897-base-pair fragment spanning the arrest site. This fragment contains an unusual sequence element, which consists of two contiguous components, a potential cruciform with stems of 6 base pairs and a d(G-A)27 X d(T-C)27 tract, and maps 1,497 to 1,564 nucleotides beyond the left junction. The possibility that this unusual sequence plays a role in the arrest of the amplification process is discussed.